Increasing Individual Resilience to Prevent Bullying in Adolescents - Netty Herawati; Nailur Rohmah; Zamzami Sabiq (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The bullying do not only take place in schools, but also in the pesantren where Islamic education is better. This condition emphasizes that to this day the bullying are still a threat, especially to the victims. There is a need for individual resilience in the face of psychological trauma as the impact of it becomes a shared responsibility, not only the pesantren but also the parents and society. Therefore, the purpose of dedication to this community is to increase the individual resilience of the victim to remove psychological trauma and prevent repetitive negotiations. The method of activities is carried out in the form of some psycho-educational activities, group discussions and counselling. The participants were followed by 49 the student pesantren, who were previously screened to distinguish between the perpetrator and the victim. Group discussions are given to both groups, the perpetrator and the victim, to identify the motives and the impact felt. Counseling is only given to the victim who is in great need to remove negative emotions and find enlightenment to rise from the negotiating trauma state. Implementation of community devotion activities from 19 August 2023 until 3 November 2023 supported by the research and community dedication institute Trunojoyo Madura University in cooperation with pesantren in Madura. The results showed an improvement in individual resilience based on pre-test and post-test scores of participants, with an effective contribution of 59.6%. It can be concluded that psycho-educational activities, group discussions and counselling can improve individual resistance in helping relieve psychological trauma and prevent repetitive bullying.Perundungan tidak hanya terjadi di sekolah, namun juga di pondok pesantren yang notabene pendidikan agama Islamnya lebih baik. Kondisi ini mempertegas bahwa sampai saat ini perundungan masih menjadi ancaman, khususnya terhadap korban. Perlunya ketahanan individu dalam menghadapi trauma psikis sebagai dampak yang ditimbulkan menjadi tanggungjawab bersama, bukan hanya lembaga pesantren namun juga orang tua dan masyarakat. Berdasarkan hal tersebut, tujuan dari pengabdian kepada masyarakat ini untuk meningkatkan ketahanan individu korban untuk menghapus trauma psikis dan mencegah perundungan berulang. Metode kegiatan dilaksanakan dalam bentuk beberapa kegiatan psikoedukasi, diskusi kelompok dan konseling. Partisipan diikuti oleh 49 santri pondok pesantren, yang diskrining sebelumnya untuk memilah antara pelaku dan korban. Diskusi kelompok diberikan kepada kedua kelompok yaitu pelaku dan korban untuk mengidentifikasi motif dan dampak yang dirasakan. Konseling hanya diberikan pada korban yang sangat membutuhkan untuk melepas emosi negative dan menemukan pencerahan untuk bangkit kembali dari kondisi trauma perundungan. Pelaksanaan kegiatan pengabdian kepada Masyarakat mulai 19 Agustus 2023sampai dengan 3 November 2023 yang didukung oleh lembaga penelitian dan pengabdian kepada masyarakat Universitas Trunojoyo Madura bekerjasama dengan pondok pesantren X. Hasil menunjukkan peningkatan ketahanan individu berdasarkan nilai pre-tes dan pos-tes partisipan, dengan sumbangan efektif sebesar 59,6 %. Dapat disimpulkan bahwa kegiatan psikoedukasi, diskusi kelompok dan konseling dapat meningkatkan ketahanan individu dalam membantu melepaskan trauma psikologis dan mencegah terjadinya perundungan berulang. Monitoring dan evaluasi dilakukan berkelanjutan melalui pembentukan konselor peer group yang diikuti santri untuk mendampingi guru BK sebagai agen perubahan.